The present status of Bewick’s Swans Cygnus columbianus bewickii in Ukraine - Chovan, Alexander A.; Kazannik, Vitaly V. (Wildfowl, 2015)
A review of the literature on Bewick’s Swans Cygnus columbianus bewickii in Ukraine indicated that it was an occasional visitor to the country during the 20th century, with small numbers recorded wintering on the northern coast of the Azov Sea. The species has occurred more regularly since winter 2006/07, with some tens of birds counted on the Dnieper River during migration and in the central Syvash on the west coast of the Azov Sea in winter months. Resting and foraging sites were identified on Kiev Reservoir, where numbers of Bewick’s Swans counted peaked at 83 individuals in November 2014. We report here for the first time the importance of the Dnieper River in providing staging sites for Bewick’s Swans in Ukraine.